Effect of metsulfuron-methyl on water quality for fish culture using water quality index - SONDHIA, SHOBHA; SINGH, PUSHPENDRA; PARMAR, VINEETA (The Indian Journal of Agricultural Sciences, 2014)
Field and laboratory experiments were conducted to evaluate the effects of herbicide on water quality through water quality index (WQI). WQI was derived to see the suitability of water in term of its quality for fishery. The WQI proposed in this study was composed of eight measurable major environmental parameters, viz. herbicide residues, pH, total dissolve solids (TDS), dissolved oxygen (DO), biological oxygen demand (BOD), free ammonia, chloride and temperature. Concentrations of these eight variables were normalized on a scale from 0 (zero) to 100 and translated into statements of water quality (excellent, good, poor, very poor and unsuitable). Based on WQI, water quality of pond adjacent to wheat field was derived as category I (excellent) to category II (good), and found to be suitable for fish farming.